Ecosystem-based management affecting Brandt's Cormorant resources and populations in the central California Current region. (January 2018) - Ainley, David G.; Santora, Jarrod A.; Capitolo, Phillip J.; Field, John C.; Beck, Jessie N.; Carle, Ryan D.; Donnelly-Greenan, Erica; McChesney, Gerard J.; Elliott, Meredith; Bradley, Russell W.; Lindquist, Kirsten; Nelson, Peter; et al.
Abstract: The Brandt's Cormorant of the California Current is a "boom-or-bust" species like its congeners in other eastern boundary, upwelling driven ecosystems, and like many of the prey upon which they depend. These birds produce many recruits when fish availability is high, leading to rapidly increasing populations, but few recruits, and may even exhibit die-offs, when the opposite is true. Unlike cormorants in the Peru and Benguela currents, however, Brandt's Cormorant population changes have yet to be correlated with those of its prey. Herein, using multi-decadal time series of cormorant colony size, diet, prey availability and mortality, in the context of changes in breeding site and fishery management, we provide insight into why central California colonies near San Francisco — a major portion of this species' global population — expanded from principally one offshore island in the 1960–70s to include a large mainland component by the 1990s. Involved were increases and decreases, respectively, of northern anchovy, a coastal forage species, and young-of-the year rockfish, more prevalent offshore. With protection of breeding sites and a shift towards ecosystem-based fisheries management by the 1990s, variations of the central California Brandt's Cormorant population are now driven naturally by forage fish availability, and perhaps inter- and intraspecific competition for prey and space when population sizes are high. This species, owing to its "boom-or-bust" natural history and the relative ease of assessing breeding population size and diet, may be ideal for monitoring the state of the central California Current food web.